2022
DOI: 10.3390/life12111908
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: An Autocidal Molecule of Plant Pathogenic Fungus

Abstract: The rise in the world’s food demand with the increasing population threatens the existence of civilization with two equally valuable concerns: increase in global food production and sustainability in the ecosystem. Furthermore, biotic and abiotic stresses are adversely affecting agricultural production. Among them, losses caused by insect pests and pathogens have been shown to be more destructive to agricultural production. However, for winning the battle against the abundance of insect pests and pathogens and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Chitosan has the ability to chelate, and bind to metals, such as some important enzyme cofactors in the growth and development of fungi that are necessary for processes related to spore germination. By depriving the fungus of metallic cofactors, various enzymatic reactions are altered and this is reflected in physiological and morphological changes in the cell (Debnath et al, 2022;Mukarram et al, 2023;Saberi et al, 2024). The results of this study coincide with those reported by various authors for the three different fungi (Carvalho et al, 2020;Kocie ¸cka and Liberacki, 2021;Segura-Palacios et al, 2021;Sun et al, 2021).…”
Section: Germinationsupporting
confidence: 90%
See 1 more Smart Citation
“…Chitosan has the ability to chelate, and bind to metals, such as some important enzyme cofactors in the growth and development of fungi that are necessary for processes related to spore germination. By depriving the fungus of metallic cofactors, various enzymatic reactions are altered and this is reflected in physiological and morphological changes in the cell (Debnath et al, 2022;Mukarram et al, 2023;Saberi et al, 2024). The results of this study coincide with those reported by various authors for the three different fungi (Carvalho et al, 2020;Kocie ¸cka and Liberacki, 2021;Segura-Palacios et al, 2021;Sun et al, 2021).…”
Section: Germinationsupporting
confidence: 90%
“…Therefore, polycationic chitosan can potentially interact with negatively charged fungal cell membrane components (phospholipids, proteins). This electrostatic interaction results in the permeabilization of the plasma membrane, interfering with the normal growth and growth metabolism of fungal structures, mycelium, and spores (Debnath et al, 2022;Mukarram et al, 2023;Saberi et al, 2024).…”
Section: Mycelial Growth Inhibitionmentioning
confidence: 99%
“…Among them, chitosan, a versatile compound, is known, even at very low concentrations, to show direct antifungal activity and trigger, as a non-microbial elicitor, the defense mechanisms in plants that are challenged by pathogens [ 11 , 24 , 25 ]. Therefore, due to the dual nature of its action, chitosan is an autocidal fungal pathogen molecule that exhibits different mechanisms of action that may be directly related to the inhibition of pathogen’s growth, fertility, and multiplication [ 28 ]. The antifungal activity of chitosan was confirmed against phytopathogenic fungi either in vitro or in planta conditions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the dual nature of its action, chitosan is an autocidal fungal pathogen molecule that exhibits different mechanisms of action that may be directly related to the inhibition of pathogen’s growth, fertility, and multiplication [ 28 ]. The antifungal activity of chitosan was confirmed against phytopathogenic fungi either in vitro or in planta conditions [ 28 ]. In regard to M. fructicola , the application of chitosan significantly reduced the disease incidence in peach fruits [ 24 ], whereas efficient control of postharvest diseases was adequately postulated upon its application [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation